Correlated factors of posttraumatic growth in patients with colorectal cancer: A systematic review and meta-analysis - Dingyuan Wei; Xue Wang; Mengxing Wang; Jiayan Wang; Fangping Chen; Luyang Jin; Xuemei Xian (International Journal of Nursing Sciences)
Objectives: This systematic review and meta-analysis aimed to identify and synthesize the factors correlated with posttraumatic growth (PTG) in patients with colorectal cancer (CRC). Methods: PubMed, Web of Science, Embase, PsycINFO, CINAHL, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang database, China Science and Technology Journal Database (VIP) and SinoMed were searched for studies that reported data on the correlated factors associated with PTG in patients with CRC from inception to September 3, 2024. The methodological quality of the included studies was assessed via the Agency for Healthcare Research and Quality (AHRQ) methodology checklist and the Newcastle-Ottawa Scale (NOS). Pearson correlation coefficient (r) was utilized to indicate effect size. Meta-analysis was conducted in R Studio. Results: Thirty-one eligible studies encompassing 6,400 participants were included in this review. Correlated factors were identified to be significantly associated with PTG in patients with CRC including demographic factors: residential area (r = 0.13), marital status (r = 0.10), employment status (r = 0.18), education level (r = 0.19), income level (r = 0.16); disease-related factors: time since surgery (r = 0.17), stoma-related complications (r = 0.14), health-promoting behavior (r = 0.46), and sexual function (r = 0.17); psychosocial factors: confrontation coping (r = 0.68), avoidance coping (r = −0.65), deliberate rumination (r = 0.56), social support (r = 0.47), family function (r = 0.50), resilience (r = 0.53), self-efficacy (r = 0.91), self-compassion (r = −0.32), psychosocial adjustment (r = 0.39), gratitude (r = 0.45), stigma (r = −0.65), self-perceived burden (r = −0.31), fear of cancer recurrence (r = −0.45); and quality of life (r = 0.32). Conclusions: This meta-analysis identified 23 factors associated with PTG in CRC patients. Medical workers can combine those relevant factors from the perspective of positive psychology, further explore the occurrence and development mechanism of PTG, and establish targeted interventions to promote PTG.